Imaging mitochondrial complex I activation during a vibrotactile stimulation: A PET study using [18F]BCPP-EF in the conscious monkey brain. Issue 12 (December 2020) - Fang, Jingwan; Ohba, Hiroyuki; Hashimoto, Fumio; Tsukada, Hideo; Chen, Feiyan; Liu, Huafeng
In order to evaluate the capability of 2- tert -butyl-4-chloro-5-6-[2-(2-[ 18 F]fluoroethoxy)-ethoxy]-pyridin-3-ylmethoxy-2H-pyridazin-3-one ([ 18 F]BCPP-EF), a novel positron emission tomography (PET) probe for mitochondrial complex I (MC-I) activity, to assess neuronal activation, an activation PET study was conducted in the conscious monkey brain with a continuous unilateral vibrotactile stimulation. PET scans with [ 15 O]H2 O, [ 18 F]BCPP-EF, or 2-deoxy-2-[ 18 F]fluoroglucose ([ 18 F]FDG) were conducted under: (1) resting conditions; (2) a continuous vibration stimulation; (3) a continuous vibration stimulation after 15-min pre-vibration; and (4) a continuous vibration stimulation after 30-min pre-vibration. The contralateral/ipsilateral ratio (CIR) in the somatosensory cortex showed significant increases in the uptake of [ 15 O]H2 O, [ 18 F]BCPP-EF, and [ 18 F]FDG with the vibration stimulation. The longer pre-vibration duration induced significantly lower CIR in regional cerebral blood flow (rCBF) measured using [ 15 O]H2 O, whereas it did not affect the CIR in [ 18 F]BCPP-EF or the regional cerebral metabolic rate of glucose (rCMRglc) measured using [ 18 F]FDG 30–60 min after the injection. These results suggest that the [ 18 F]BCPP-EF response in the later phase of scans was not influenced by the increase in rCBF, indicating the capability of [ 18 F]BCPP-EF to detect acute changes in MC-I activity induced by neuronal activation. However, the metabolic shift from glycolysis to oxidation was not observed under the stimulation used here.